On Board Training Program Management for Deck and Engine Cadets of PIP Semarang - Irma Shinta Dewi; Rusdarti Rusdarti; Tri Joko Raharjo; Titi Prihatin (Universitas Negeri Semarang, 2021)
On Board Training (OBT) is the implementation of marine real working practices on commercial or merchant ships by cadets of the Deck and Engineering study program in the 5th and 6th semester. It is to train skills, to improve skills, and also to have real life live on commercial ships directly. Politeknik Ilmu Pelayaran (PIP) Semarang organizes OBT which is carried out by cadets in cooperation with domestic and foreign shipping companies. This study will examine the management of the OBT program conducted by Students’ Affairs and Alumni Sub Division of PIP Semarang. The objective of the research is to describe the management program of OBT for fifth and sixth semester cadets of PIP Semarang. This type of research is qualitative research with descriptive field research to complete the data and compare with the data that has been found through observation, interview, questionnaires, and documentation, while the analysis of research data, namely data reduction, data presentation, and conclusion. The results of the study showed that the program management of OBT includes; (a) the planning phase of the OBT program includes; make a program activity plan, record the number of cadets who will practice, complete the requirements of pre-practice documents, (b) the implementation stage of the OBT program includes; practice by cooperating with domestic and foreign shipping companies, (c) the evaluation phase of the OBT program includes; monitoring the implementation of practices; cadets provide reports to the Students’ Affairs and Alumni Sub Division, cadets complete the requirements of post-practice documents, check Cadet Record Books (CRB) and Practice Work Papers, provide a certificate of completion, and collect post-OBT documents. The conclusion is the program management conduct planning, implementation, and evaluation of the program in line with the Standard Operation Procedure (SOP) of Students’ Affairs and Alumni Sub Division of PIP Semarang.